Active case finding for tuberculosis in tea gardens of Bangladesh: A cross-sectional survey - Arifa Nazneen; Tanjina Rahman; Aazia Hossain; Anjan Kumar Saha; Ahammad Shafiq Sikder Adel; Asif Mujtaba Mahmud; Khalequ Zaman; Azharul Islam Khan; Aung Kya Jai Maug; Shahriar Ahmed; Sayera Banu (PLoS ONE, 2025)
Tea garden populations with poor socio-economic status are at risk of developing TB. The active case finding (ACF) approach is effective in finding TB among the people at risk. We have conducted ACF for TB to find people with presumptive TB in the tea gardens of Sylhet division to identify TB disease. It was a cross-sectional survey conducted at the household level, in the randomly selected three tea gardens of Sylhet division. The selected population was 20,215 and was screened for TB presumptive symptoms between July and Oct 2022. Each presumptive had required TB testing, which includes GeneXpert MTB/RIF (Xpert) or Sputum microscopy, X-ray, and Fine Needle Aspiration Cytology (FNAC) if there was gland swelling. Around 99.6% (20,127/20,215) of the surveyed population were screened for TB. Among the screened population, gender distribution was almost equal, and 34% had no education. And people with presumptive TB were 0.8%; among them, most (91%) were pulmonary TB presumptive with male predominance. Among all presumptive, 87.4% had a cough for ≥ 14 days and 78% had a fever. We identified a total of 17 pulmonary TB; among them, bacteriologically confirmed TB were only 6 (35.3%). The estimated proportion of TB among the surveyed population was 0.10%. The findings suggest a need for sustained TB screening activities integrated with community involvement.